SAT0513 Brainstem Auditory Evoked Potentials and Visual Potentials in Kawasaki Disease: Expression of CNS Vasculitis?. (9th June 2015) - Maggio, M.C.; Ministeri, C.M.; Maccora, I.; Vitaliti, G.; Prinzi, E.; Corsello, G.
Abstract : Background: Kawasaki disease (KD) is an acute, self-limited vasculitis of infants and children that is nowadays the most common cause of acquired heart disease in children. Transient sensorineural hearing loss (20 to 35 dB) is a possible complication of acute phase KD and may be related to salicylate toxicity in some patients. Objectives: Brainstem Auditory Evoked Potentials (BAEPs), and Visual Evoked Potentials (VEPs) were examined in 43 children (age: 0, 8-7, 5 years) affected by KD. No risk factors for hearing loss and/or neurological impairment of CNS were identified in all the patients. BAEPs showed altered waves II to V, in 18 patients (42%). Among these, in 4 patients (20%) VEPs showed altered waves. Results: The 18 patients with altered waves of BAEPs were 11 with typical KD, 7 with incomplete KD. Among the 11 patients with altered BAEPs and typical KD, 36% showed coronaritis; among the 7 patients with altered BAEPs and incomplete KD, 57% showed coronaritis. The evaluation of waves VI, VII, interpeak latency V-VII were performed in all the patients and showed a pathological pattern in 72% of altered BAEPs, but also in 68% of patients with normal waves I to V. These waves are expression of neuronal conduction in medial geniculate, acoustic radiations, sign of a lesion of mesencephalon, thalamus and/or acoustic radiations. No correlation was relieved with EVIG doses, days of fever at the start of EVIG, pre-EVIG D-Dimer plasmatic levels, CRP, ESR, leukocytes, neutrophils percentage pre- and post- EVIG. Conclusions: Altered BAEPs waves are relieved in 81% of KD patients; 70% of KD patients showed altered VI, VII and/or V-VII expression of CNS vasculitis of mesencephalon, thalamus and/or acoustic radiations. Despite normal hearing acuity these children showed a vasculitis of CNS, in 43% of them coronaritis was associated. References: Knott PD, Orloff LA, Harris JP, Novak RE, Burns JC; Kawasaki Disease Multicenter Hearing Loss Study Group. Sensorineural hearing loss and Kawasaki disease: a prospective study. Am J Otolaryngol. 2001;22(5):343-8. Disclosure of Interest: None declared